ChemInform Abstract: One Pot Synthesis of Pyran‐Based Heterocycles from Benzyl Halides as Key Reagents. Issue 34 (August 2015) - Beerappa, Mallappa; Shivashankar, Kalegowda
Abstract A three‐component coupling reaction of aldehydes, formed in situ by oxidation of benzylic halides, with active methylene compounds and α‐hydroxy C—H acids yields fused pyran derivatives.